2000
DOI: 10.1089/neu.2000.17.421
|View full text |Cite
|
Sign up to set email alerts
|

Three Months of Chronic Ethanol Administration and the Behavioral Outcome of Rats After Lateral Fluid Percussion Brain Injury

Abstract: This study examined the effects of 3 months of chronic ethanol administration (CEAn) on the behavioral outcome in rats after lateral fluid percussion (FP) brain injury. Rats were given either an ethanol liquid diet (ethanol diet groups) or a pair-fed isocaloric sucrose control diet (control diet groups) for 3 months. Then, rats from both diet groups were subjected to either lateral FP brain injury of moderate severity (1.8 atm) or to sham operation. Postinjury behavioral measurements revealed that brain injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…Additionally, behavioral abnormalities similar to those found in humans with Type C HE were observed in these rats, including drowsiness, decreased wakefulness and attentiveness, and impaired grooming and exploratory behavior. While animals with Type C HE were behaviorally defective, no evidence of severe distress, such as intense pain, muscular spasms, fainting, or breathing difficulties, was observed, consistent with features associated with Type C HE in humans, as well as with observations by other investigators in experimental animals [49][50][51]56,57,[59][60][61]. These findings strongly suggest that young/aged male rats are more prone to develop TAA-induced Type C HE as compared to adult males or young or aged females.…”
Section: Effect Of Taa On the Motor And Cognitive Functionssupporting
confidence: 87%
“…Additionally, behavioral abnormalities similar to those found in humans with Type C HE were observed in these rats, including drowsiness, decreased wakefulness and attentiveness, and impaired grooming and exploratory behavior. While animals with Type C HE were behaviorally defective, no evidence of severe distress, such as intense pain, muscular spasms, fainting, or breathing difficulties, was observed, consistent with features associated with Type C HE in humans, as well as with observations by other investigators in experimental animals [49][50][51]56,57,[59][60][61]. These findings strongly suggest that young/aged male rats are more prone to develop TAA-induced Type C HE as compared to adult males or young or aged females.…”
Section: Effect Of Taa On the Motor And Cognitive Functionssupporting
confidence: 87%
“…There is some evidence to suggest that a dosedependent relationship may exist, with higher BAL being associated with lower post-injury cognitive functioning (Tate et al, 1999). There is also evidence from recent animal studies that suggests that at lower or moderate doses, alcohol may have a neuroprotective effect (Janis et al, 1998;Kelly et al, 1997aKelly et al, ,b, 2000 or limited effect (Masse et al, 2000;Taylor et al, 2002) on cognitive functioning and structural changes following TBI. Clearly this is an important area for further investigation.…”
Section: Interactive Effects Of Alcohol and Tbi Hypothesismentioning
confidence: 99%
“…19,42,43 Animal studies have suggested that at lower or moderate doses, alcohol may have a neuroprotective effect, 5,44 -46 although others have contended that the effect on cognitive performance and structural changes after head injury may be limited. 47,48 Our findings suggest that a mortality benefit because of the presence of alcohol may exist. The possible rationales for this result are not yet well defined.…”
Section: Discussionmentioning
confidence: 67%